The influence of television advertisements on children in Petaling Jaya / Tan Mei Lin, Suzie - Tan, Mei Lin, Suzie (1986)
The purpose of this study was to examine the degree of influence that television advertising have on children in Malaysia, focusing specifically on children in Petaling Jaya. Private groups, government, regulatory agencies, consumer advocates, and social critics have been making a wide range of comments about the content and presumed impact of advertisement. This study was conducted in order to identify advertisements which influence children and to specifically examine the contents of these advertisements in order to study the nature and extents of their influence. The age and income backgrounds of the respondents are also dealt with here as variables, in an attempt to identify their significance in determining the influence of advertisements on children. It was also the aim of this study to indicate the effects of television advertising on children so that appropriate steps can be made, if necessary, to achieve a truthful, accurate and fair advertising industry. It is hoped that these findings, however tentative and limited, will be useful to those who are concerned with "advertising to children". It is also hoped that these findings will be helpful in the mounting of other studies on children's perception towards advertising.